Life and Value of Remote Working: Defining Well-being in Digitized Era of Young Employee Malang - Agatta, Shilvi Khusna Dilla; Triratnawati, Atik (Universitas Padjadjaran, 2025)
The aim of this study is to examine the mental well-being of young remote workers in Malang City through social interactions, expectations, and self worth. As an evolving work system in Indonesia, remote work still presents challenges, both in terms of technology and social dynamics. Young employees who are in the career development stage at the age of 23-29 are often caught up in trying to achieve high productivity and maximum happiness, which sometimes triggers burnout. Through an anthropological approach with qualitative methods, this research utilises semi-structured interviews by highlighting remote employee perspectives on mental well-being and considering the values and experiences of work culture in a virtual work environment. The different experiences and definitions of well-being for young remote employees depend on their individual perspectives, backgrounds and working conditions, making the results of this study subjective. The results show that the mental well-being of remote workers cannot be separated from the Javanese social and cultural context that emphasises collective happiness. On that basis, this research is expected to contribute to the development of subjective well-being studies in the field of anthropology.